Rytuały ofiarne w starożytnym Rzymie na podstawie „Nocy attyckich” Aulusa Gelliusza. Wybrane zagadnienia - Kowalska, Martyna (Collectanea Philologica, 2025)
The article discusses selected issues related to sacrificial rituals in ancient Rome based on Aulus Gellius’ Attic Nights. The work focuses primarily on information related to the circumstances and reasons for making some sacrifices, the age of sacrificial animals, as well as linguistic curiosities related to sacrificial rituals. The antiquarian characterizes, among other things, what hostiae maiores, succidaneae, praecidaneae and bidentes were, and also explains that it is not clear to which deity a sacrifice should be made in connection with the occurrence of an earthquake.